EDUCATION POLICY ANALYSIS IN ACCESS TO GOVERNMENT REGULATION NO 17 YEAR 2010 - Mutia Ulfa (Sunan Kalijaga International Journal on Islamic Educational Research, 2019)
Access to education refers to the government regulation No. 17 of 2010 on the expansion and equitable access to education. Pemerintahah able to pursue that whole communities are able to obtain the same rights to education in both urban and rural areas. There are several products that include equity and equal access to education, namely; infrastructure standards, standards development level of achievement, the standard scope of development, lesson planning standards, standardized implementation of learning, learning assessment standards, standards kualisifikasi educators and education personnel, standardized management and financing standards. Further products in the distribution and access to education dianlisis from various perspectives, namely; economic analysis, political analysis, analysis of socio-cultural, and administrative analysis.